STRATEGY FOR DEVELOPMENT AND REVITALIZATION OF BANYUMULEK POTTERY INDUSTRY, WEST NUSA TENGGARA WITH AN INTEGRATED APPROACH BASED ON TOURISM AND CREATIVE ECONOMY - Amboro, Joko Lulut; Wahyuningsih, Novita; Abdilah, Admiral Akhir (MATTER: International Journal of Science and Technology, 2018)
This study is aimed to determine the development of pottery industry, the factors that influence the development of pottery industry, and to formulate the appropriate development and revitalization strategy for the community of potters in Banyumulek, West Nusa Tenggara. The type of research used is qualitative research with Focus Group Discussion method, and field visits (survey), which take place at Banyumulek Pottery Industrial Center. The result of the research shows that the industry of pottery in Banyumulek Village undergoes prospective development. The formulation results of community empowerment strategy in the form of program planning are: (1) establishment of community to preserve pottery industry, (2) innovative entrepreneurship training and pottery-making skills; (3) development of marketing methods and (4) a tourism-based and creative economy approach.